Ovine red cell concentrates for transfusion research – is the storage lesion comparable to human red cell concentrates?. Issue 5 (26th October 2020) - Simonova, Gabriela; Wellburn, Rebecca; Fung, Yoke Lin; Fraser, John F.; Tung, John‐Paul
Abstract : Background and objectives: Sheep are increasingly being used as a large in vivo animal model of blood transfusion because they provide several advantages over small animals. Understanding the effects of storage duration on ovine (ov) red cell concentrates (RCCs) and how these changes compare with stored human (hu) RCCs is necessary to facilitate clinical translation of research findings. Materials and methods: OvRCCs ( n  = 5) collected and processed in standard human blood collection packs, and equivalent huRCCs provided by Australian Red Cross Lifeblood ( n  = 5), were stored at 2–6°C for 42 days, with samples collected weekly. Haemolysis index was determined by measuring supernatant haemoglobin concentration. Biochemical parameters were evaluated using a blood gas analyser. Energy metabolites and biologically active lipids were measured using commercial assays. Osmotic fragility was determined by lysis in various saline concentrations. Extracellular vesicles were characterized by nanoparticle tracking analysis. Results: Ovine red blood cells (RBCs) are double in number, smaller in size and more fragile than human RBCs. Haematological values were unchanged throughout storage. In contrast, biochemical and metabolic values, and haemolysis index in three of the five ovRCCs exceeded huRCCs licensing criteria by day 42. Accumulation of extracellular vesicles and biologically active lipids was comparable between huRCCs and ovRCCs. Conclusion: This study documents similarities and differences in the storage lesion of ovRCCs and huRCCs. This new information will guide the design of ovine transfusion models to enhance translation of findings to human transfusion settings.